Novel halogenated pyrido[2, 3-a]carbazoles with enhanced aromaticity as potent anticancer and antioxidant agents: rational design and microwave assisted synthesis. (25th October 2019) - Saravanabhavan, Munusamy; Badavath, Vishnu Nayak; Maji, Siddhartha; Muhammad, Shabbir; Sekar, Marimuthu
Abstract : Design and synthesis a series of pyrido[2, 3- a ]carbazoles for their anticancer and antioxidant activity. Abstract : Design and synthesis of a novel series of 4 a, 5, 6, 11-tetrahydro-4 H -thieno[3′, 2′:5, 6]pyrido[2, 3- a ]carbazol-4-one derivatives (3a–3g ), and evaluation of their anticancer activity (HeLa, MCF-7 and HEp-2 cell lines by MTT assay method) and antioxidant (DPPH and ˙OH radical scavenging) activity. The designed compounds (3a–3g ) were synthesized using microwave irradiation in the presence of p -TsOH, with yields up to 91%, in a short time (11 min). Halogenated compounds (3e and 3f ) strongly bind with the calf thymus (CT)-DNA helix via intercalation and show more hypochromicity (84% and 81% respectively) with a red shift (12 nm and 10 nm, respectively). Compounds (3e and 3f ) completely cleaved pBR322 DNA by oxidative cleavage. In general, it was observed that chloro and bromo substituted compounds 3e and 3f show excellent anticancer activity and strongly bind to CT-DNA, which may be due to the stronger electron withdrawing tendency of the chloro and bromo groups than that of the electron donating and unsubstituted carbazole derivatives. The most potent compounds 3e (2.05, 3.35, and 10.24 fold) and 3f (3.62, 6.28 and 8.09 fold) displayed stronger cytotoxicity than the positive control cisplatin, and also compared with ellipticine. Compound 3g with –OCH3 substitution and 3e with chloro substitution exhibited greater antioxidant activity than standard ascorbic acid. All the designed compounds were well accommodated in the ATP-binding site of human CK2 protein (Asn118, Ile174, Val53, Val116). The adopted design strategy provided two potent halogenated compounds (3e and 3f ), which may require further in vivo investigations before subjecting to clinical trials, and also some useful insights about the future design of more potent inhibitors for the treatment of cancer.